Synthesis of Some Dimers of Substituted Oxazolin-5-ones - D. Prabhavat, Manoj (Asian Journal of Chemistry, 2010)
Substituted 1,2-bis-(2-methyl/phenyl-4-arylidene-d 2-imidazolin- 5-one-1-yl) ethane were synthesized from the reaction of diamino ethane with 2-methyllphenyl-4-arylidene-oxazolin-5-ones in acidic ethanol.